Repartição espacial da comunidade de aves em um fragmento florestal no município de Ivinhema (MS) - CONCEIÇÃO, Tamiris Paioli; RUY, Andressa Aparecida Araujo; GIMENES, Márcio Rodrigo (ANAIS DO ENIC, 2018)
-